Contesting Marriage Legitimacy: Customary Marriages and Islamic Family Law in Mandailing Natal - Affan Muhammad Hasibuan; Asrofi Asrofi; Suroto Suroto; Deri Darmawan Lubis (Jurnal Hukum Keluarga, 2026)
This study examines customary marriage in Mandailing Natal as a form of living law that shapes kinship relations, social legitimation, and dispute resolution. Using a normative–empirical socio-legal design, the research triangulates doctrinal analysis of Islamic family-law sources, notably ‘urf and maqasid al-shari’ah, with field evidence on Dalihan Na Tolu procedures, ceremonial practice, consent dynamics, and local adjudication. The results show that many customary mechanisms, such as collective deliberation and the customary dowry (mahar), substantively align with core objectives of Islamic family law and may be classified as ‘urf sahih, insofar as they advance lineage protection, dignity, and contractual certainty. Nevertheless, evolving social pressures produce misalignments, particularly around free and informed consent, equitable allocation of marital entitlements, and the legal visibility of customary marriages in Mandailing Natal. To address these tensions the study recommends inclusive, maqasid al-shari’ah-informed interventions: clearer documentation of consent and mahar, stronger links between customary authorities and civil registration, and targeted legal literacy for women and customary leaders. Scientifically, this study contributes an integrated ‘urf and maqasid al-shari’ah evaluative framework grounded in empirical data, offering both theoretical refinement and actionable policy guidance for reconciling living custom with the protective aims of Islamic family law.